Mapeamento de competências necessárias aos chefes de Parques Nacionais: uma proposta a partir do modelo de Cheetham e Chivers - Aurich, Katia Regina (2017)
This research had as general objective to map the necessary competencies for the position of head of national park, one of the twelve categories of Conservation Units existing in Brazil, managed by the Chico Mendes Institute of Biodiversity Conservation – ICMBio. The national parks are conservation units whose basic objective is the preservation of natural ecosystems of great ecological importance and scenic beauty, carrying out scientific research and the development of activities of education and environmental interpretation, recreation in contact with nature and ecological tourism. Through a qualitative methodology with the application of semi structured interviews and using an interpretative analysis from coding (Gibbs, 2009) the final product was generated, a map of competencies for the role of head of national park that could be applied in the selection of servers for the position and also to guide the development of competences, whose content inserts it in the line of research Operations Management in Public sector.